2017
DOI: 10.18632/oncotarget.15644
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA-21 in radiosensitivity in non-small cell lung cancer cells by targeting PDCD4 gene

Abstract: This study aims to explore the effects of microRNA-21 (miR-21) on radiosensitivity in non-small cell lung cancer (NSCLC) by targeting programmed cell deanth 4 (PDCD4) and regulating PI3K/AKT/mTOR signaling pathway. Cancer tissues and adjacent normal tissues were collected from 97 NSCLC patients who received a standard radiotherapy regimen. TUNEL assay was applied to determine cell apoptosis in tissues. The qRT-PCR assay was used to detect the expressions of miR-21 expression and PDCD4 mRNA. The protein express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…Studies show that miRNA molecules such as miR-181a and miR-140-5p are important in autophagy regulation (19,20). It is reported that miR-21 is able to regulate the drug resistance of NSCLC (21). Therefore, it is hypothesized that miR-21 may participate in the occurrence and development of NSCLC by regulating autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that miRNA molecules such as miR-181a and miR-140-5p are important in autophagy regulation (19,20). It is reported that miR-21 is able to regulate the drug resistance of NSCLC (21). Therefore, it is hypothesized that miR-21 may participate in the occurrence and development of NSCLC by regulating autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Downregulation of PDCD4 is associated with a poor prognosis. miRNAs, such as miR-21 and miR-183, target PDCD4 (6,30,41). In this study, the importance of miR-96 was revealed by microarray analysis of clinical samples, where miR-96 was demonstrated to be upregulated in GBM cases compared with normal tissues (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…1A). Therefore, the miR-96 expression was further analyzed in an array of GBM cell lines (U87-MG, U251-MG, A172 and T98g), which have been reported to have varying radiosensitivity (30). As illustrated in Fig.…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In terms of downregulation of proteins, miRNA-21 has been reported to specifically target tumor suppressors such as PTEN, 15 Bcl-2, 15 Smad7, 16 and PDCD4. 17 Long non-coding RNAs (lncRNAs) play crucial roles in many diseases via controlling gene expression. 18 One of their mechanisms of action involves the formation of regulatory networks with other RNA species, such as miRNAs and mRNAs.…”
Section: Introductionmentioning
confidence: 99%